Auditing of Danish pig herds for controlled housing requirements and Trichinella - Lis Alban; Heidi Enemark; Heidi Huus Petersen; Lisbeth Harm Nielsen (Food and Waterborne Parasitology)
Trichinella is a zoonotic parasite, which historically has been of large concern for public health in Europe. Consequently, testing of all pigs for Trichinella has been mandatory in many European countries, even though Trichinella is almost exclusively found in outdoor or backyard production. The idea therefore emerged that auditing for biosecurity should replace testing in indoor production. In the European Union (EU), pigs raised under so-called controlled housing conditions are exempt from testing. The specific requirements for a pig production to be considered a controlled housing holding are described in Annex IV in the EU Trichinella Regulation No. 2015/1375. In Denmark, the controlled housing concept is used extensively, not to omit Trichinella testing but to allow visual-only post-mortem inspection at export-authorized abattoirs. The Danish pig industry has established a quality assurance scheme called DANISH Product Standard, which is used to assure that the pig production maintains specific standards. This paper describes how the control, including the auditing, is set up and shows how the EU requirements regarding controlled housing are controlled. Moreover, the EU requirements are compared with the recommendations issued by the International Commission on Trichinellosis and the World Organisation for Animal Health. Finally, strengths, weaknesses, opportunities and threats of the Danish way of documenting indoor finisher herds' compliance with controlled housing as specified by the EU are discussed. It is concluded that the validity of the system is high.